Genotype dynamic for agent neuroevolution in artificial life model - Zavertanyy, V.; Makarenko, A. (Системні дослідження та інформаційні технології, 2017)
Cooperation behavior is one of the most used and spread Multi-agent system feature. In some cases emergence of this behaviour can be characterized by division of population on co-evolving subpopulations [1], [2]. Group interaction can take not only antagonistic conflict form but also genetic drift that results with strategies competition and assimilation [3]. In this work we demonstrate different relation between agent grouping and they behavior strategies. We use approach proposed in work [2] methodology of agent genotype dynamic tracking, due to this approach the evolving population can be presented in genotype space as a cloud of points where each point corresponds to one individual. In current work consider the movement of population centroid – the center of the genotype cloud. Analysis of such trajectories can shad the light on the regimes of population existence and genesis.